Determination of the Fractal Dimension of CO2 Adsorption Isotherms on Shale Samples. (22nd February 2022) - Qi, Hongyan; Wang, Zhenlin; Yu, Jianglong; Yu, Peirong; Zheng, Guoqing
Abstract : The fractal theory has been widely applied to the analysis of gas adsorption isotherms, which are used for the pore structure characterization in unconventional reservoirs. Fractal dimension is a key parameter that can indicate the complexity of the pore structures. So far, most fractal models for gas adsorption are for N2 adsorption, while fractal models for CO2 adsorption are rarely reported. In this paper, we built a fractal model for CO2 adsorption by combining a thermodynamic model and the Dubinin–Astakhov model. We then applied the new model to three CO2 adsorption isotherms measured on shale samples. The results show that the fractal dimension from the new model lies between 2 and 3, which agrees with the fractal geometry. The new model presented in this paper can be used for the CO2 adsorption analysis, which allows characterizing micropore structures in shales.